Tradição e desenvolvimento: a chegada da cidade à vila - Andrade, Eduarda de Lima (2014)
Our goal is to speak about the limits of development in a fragmented area for various uses, but it is labeled as traditional. This area, our object of study, is the village of Ponta Negra located in the neighborhood of Ponta Negra, Natal RN. The Village, the poorest part of the district is also the largest in socio-spatial contrasts. From the 1970s the site was no longer the city around Natal, becomes part of the expansion project of the city to the south. With the project for the development of tourism in Rio Grande do Norte, deployed by PRODETUR (1993), the Village shall be directed by its urbanization for "touristification". One of the main uses of the housing boom was through the dispossession of communal lands that were previously. The "new" land use modifies the structure of the local productive system and consequently the social organization of the village. This social organization, considered as traditional, becomes part of an "ideal" tourism scene. The problem starts when the tradition is presented as a tourist souvenir, and not as productive system. The tradition made object, and not as a way of life, shaping the space of the Village, and that modeling makes clear sociospatial consequences promoted by the type of "tourist" urbanization on site. Much of the local discourse, civil society and academia to foster corroborate the idea of tradition as an object of "preservation", constructing a discourse that does not fit with the reality of the place. Think and describe the tradition as a temporal category (before and after), leaving aside the analysis that the very idea of tradition is used as a (modern) strategy artificial creation of "traditional space". For this purpose, specific objectives follow the relationship between development and underdevelopment tradition to compose a critique of the idea of tradition as opposed to the modern way of life. Thus, we associate the traditional way of life as peripheral modernity; identify behind the discourse of tradition Vila training its periphery; and describe our object of research as a case history of the development of the modern capitalist system. Thus, our central problem is to think the limits of development areas in ideologically conceptualized in a way, but in their daily lives appear on another reality.